The use of innovative methods in the systemic development of the cognitive competence of future teachers in the system of preschool education - Abdujalilova Odinaxon Mirzaabdulla qizi (Zien Journals, 2023)
the article reveals the problem of advanced training of a modern teacher of preschool education, on the basis of a structural-functional approach, the main components and conditions for the development of professional competence of teachers of preschool education are revealed. Abstract: the article describes the problem of improvement of professional personal development of the modern teacher of preschool education; on the bases of structural and functional approach it is implemented to obtain the main components and conditionals of improvement of teachers' professional competence of system of preschool education.
Keywords: pedagogical competence; integration; motivation; theoretical